2006
DOI: 10.1021/es061040r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Gold Bioaccumulation by Filamentous Cyanobacteria from Gold(III)−Chloride Complex

Abstract: The mechanisms of gold bioaccumulation by cyanobacteria (Plectonema boryanum UTEX 485) from gold(III)-chloride solutions have been studied at three gold concentrations (0.8,1.7, and 7.6 mM) at 25 degrees C, using both fixed-time laboratory and real-time synchrotron radiation absorption spectroscopy (XAS) experiments. Interaction of cyanobacteria with aqueous gold(III)-chloride initially promoted the precipitation of nanoparticles of amorphous gold(I)-sulfide at the cell walls, and finally deposited metallic go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
116
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(125 citation statements)
references
References 31 publications
(41 reference statements)
7
116
0
2
Order By: Relevance
“…X-ray absorption near edge structure (XANES) spectra collected from cell pellets after 6 h of exposure to Au(III)-complexes showed that 100 wt% of the accumulated Au was converted to a Au(I)-S species (Fig. 3 and SI Materials and Methods), as was observed in cyanobacteria (19). Linear combination fitting (LCF) of spectra collected after 72 h to model spectra showed that 53.0 wt% of Au were present as Au(I)-S, 28.7 wt% as metallic Au 0 , and 18.3 wt% as Au(I)-C (Fig.…”
Section: Si Materials and Methods)mentioning
confidence: 74%
“…X-ray absorption near edge structure (XANES) spectra collected from cell pellets after 6 h of exposure to Au(III)-complexes showed that 100 wt% of the accumulated Au was converted to a Au(I)-S species (Fig. 3 and SI Materials and Methods), as was observed in cyanobacteria (19). Linear combination fitting (LCF) of spectra collected after 72 h to model spectra showed that 53.0 wt% of Au were present as Au(I)-S, 28.7 wt% as metallic Au 0 , and 18.3 wt% as Au(I)-C (Fig.…”
Section: Si Materials and Methods)mentioning
confidence: 74%
“…Oat (Avena sativa) biomass was also found to recover Au (III) ions from aqueous solutions and reduce Au (III) to Au (0), forming Au nanoparticles (Armendariz et al, 2004(Armendariz et al, , 2009). Synthesis of nanogold has also been reported in algae, including Chlorella vulgaris (Ting et al, 1995), Sargassum wightii (Singaravelu et al, 2007) and Plectonema boryanum (Lengke et al, 2006a(Lengke et al, , 2006b). Gold nanoparticle synthesis by cyanobacteria (such as Lyngbya majuscula and Spirulina subsalsa), green algae (Rhizoclonium hieroglyphicum and R. riparium) and diatoms (Nitzschia obtusa and Navicula minima) has recently been reported by Chakraborty et al (2006Chakraborty et al ( , 2009 and Nayak et al (2006), and biosynthesis of gold nanorods by Nostoc ellipsosporum by Parial et al (2012).…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, second generation nanotechnology is focused towards clean technologies that minimize possible environmental and human health risks associated with manufacture and fabrication; there is an ever-growing demand for development of clean, nontoxic, and environmentally benign synthesis procedures. Microorganisms, including bacteria, fungi and algae, have been proposed as potential eco-friendly nano-factories for the synthesis of metal, including gold, nanoparticles (Nair & Pradeep, 2002;Lin et al, 2005;Lengke et al, 2006aLengke et al, , 2006b.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal pollution represents an important environmental problem because of toxic effects of metals. Interest in the development of metal removal by biosorption using microorganisms is shown in literature [1][2][3][4][5][6][7][8][9][10][11]. Cyanobacteria (blue green algae) represent the largest and most diverse group of photosynthetic prokaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Some bacteria have evolved the mechanisms of detoxication of heavy metals, and some even use them for respiration. In [9] the recovery of gold using algae cells was investigated, and in [10,11] the microorganism-gold interaction was studied. The investigation of the efficacy of the metal uptake by the microbial biomass is essential for the industrial application of biosorption.…”
Section: Introductionmentioning
confidence: 99%